بناء أنموذج برمجه خطيه عددية صحيحة لزيادة الإرباح في خط إنتاجي للزيوت النباتية السائلة - موسى سعد (Journal of Kufa for Mathematics and Computer, 2012)
Most Iraqi companies in the manufacturing sector face a problem of low profits and costs increasing because this sector did not use scientific techniques. In this paper an integer programming model was built to solve the profit problem in the liquid vegetable oil production in the state company of vegetable oils. The branch and bound method was used to solve this model. تواجه معظم شركات القطاع الصناعي في العراق مشكله قله الإرباح وزيادة التكاليف لان هذا القطاع لا يستخدم الأساليب العلمية ضمن هذا البحث بناء أنموذج برمجه عدديه صحيحة لحل مشكله قله الإرباح في خط إنتاجي للزيوت النباتية ألسائله في الشركة العامة للزيوت النباتية وقد استخدمت طريقه التفرع والتقيد لحل الأنموذج الرياضي